"Buenos Aires beat": A topography of rock culture in Buenos Aires, 1965-1970 - Sanchez Trolliet, Ana Belen (2014)
In this article, I examine the rise of 'countercultural rock' in the city of Buenos Aires between 1965 and 1970. Through the identification, mapping and analysis of real and imaginary spaces, I analyse how rock occupied the city both materially and symbolically. This dual approach to the study of the production, circulation and consumption of rock music enables us to understand a paradox which spanned those formative years: although it was postulated as the genre of modern Buenos Aires, its aesthetic was geared towards constructing an anti-urban account that favoured escape towards idealized natural environments.